Bibliometric analysis of scientific production on the use of remotely piloted aircraft in agricultural spraying - Ribeiro, Maria Eduarda Audizio; Ribeiro, Luis Felipe Oliveira; Santos, Thales Gomes dos; Nunes, João Guilherme Pereira; Vitória, Edney Leandro da (Brazilian Journal of Production Engineering, 2024)
The use of remotely piloted aircraft (RPA) in agricultural sector for spraying operations and the application of agricultural pesticides and fertilizers is continually expanding. As a result, the need for technical-scientific research becomes increasingly evident. The objective was to conduct a survey of information related to this theme, utilizing bibliometric analysis. This analysis was carried out using scientific publications obtained from the Scopus database, employing terms such as UAV, UAS, drone, deposition, RPA, flight, agriculture, and speed. Data analysis was performed using the VOSviewer software. China and the USA are the countries that concentrate the majority of scientific publications, comprising approximately 87% of the selected studies during the period from 2013 to 2023. Terms such as “Unmanned Aerial Vehicle” (UAV) were widely used in the year 2019.5, while words like “aerial spraying”, “drones”, and “plant protection” only gained citation relevance in the year 2021. Research and scientific documents have evolved over time, influenced by contributions from authors in various countries.